Pulvinus functional traits in relation to leaf movements: A light and transmission electron microscopy study of the vascular system - Rodrigues, Tatiane A.; Machado, Silvia R. (Pergamon-Elsevier B.V. Ltd, 2008)
Previous studies on legume pulvini suggest that the vascular system plays an important role in the redistribution of ions and transmission of stimuli during leaf's movements. However, the number of anatomical and ultrastructural studies is limited to few species. The aim of this paper is to investigate the structure and cellular features of the pulvinus vascular system of nine legume species from Brazilian cerrado, looking for structural traits pointing to its participation in the leaf's movements. Samples were excised from the medial region of opened pulvinus of Bauhinia rufa, Copaifera langsdorffii, Senna rugosa (Caesalpinioideae), Andira humilis, Dalbergia miscolobium, Zornia dilphylla (Faboideae), Mimosa rixosa, Mimosa flexuosa and Stryphnodendron polyphyllum (Mimosoideae), and were prepared following light microscopy, transmission electron microscopy and histochemical standard techniques. The vascular system occupies a central position, comprises phloem and xylem and is delimited by a living sheath of septate fibers in all the species studied. This living cells sheath connects the cortex to the vascular tissues via numerous plasmodesmata. The absence of fibers and sclereids, the presence of phenolic idioblasts and the abundance and diversity of protein inclusions in the sieve tube members are remarkable features of the phloem. Pitted vessel elements, parenchyma cells with abundant cytoplasm and living fibriform elements characterize the xylem. The lack of lignified tissues and extensive symplastic continuity by plasmodesmata are remarkable features of the vascular system of pulvini of the all studied species. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: fabaccae; leaf movement; pulvinus; structure; vascular system